Recent advances in the fabrication of graphene-ZnO heterojunctions for optoelectronic device applications - Liang, Feng-Xia; Gao, Yang; Xie, Chao; Tong, Xiao-Wei; Li, Zhong-Jun; Luo, Lin-Bao (Journal of materials chemistry. C, Materials for optical and electronic devices, 2018)
Recently, by taking advantage of the synergistic effects of both graphene and ZnO, various photoelectric devices that combine graphene and ZnO have exhibited excellent device performances and attracted increasing research interest. However, although significant achievements have been made, many challenges still exist. In this review paper, we comprehensively summarize the recent advances in the fabrication of various graphene (also including reduced graphene oxide)-ZnO ( e.g. ZnO films, nanowires, nanotubes, nanorods etc. ) hybrid heterostructures, and their application in a number of optoelectronic devices, including photodiodes, phototransistors, solar cells, light emitting diodes (LEDs), lasers and so on. We start by briefly surveying the recent progress in the fabrication methodologies such as low-temperature and high-temperature methods. And then, we will elaborate on the optoelectronic device application in terms of device physics, performance analysis, and device optimization approaches. Finally, we close with some unresolved issues and challenges in this field. Recently, by taking advantage of the synergistic effects of both graphene and ZnO, various photoelectric devices that combine graphene and ZnO have exhibited excellent device performances and attracted increasing research interest.